Chronic epidural hematoma: a systematic review and meta-analysis - Nicaise Kpègnon Agada; Nourou Dine Adeniran Bankole; Mèhomè Wilfried Dossou; Omar Boladji Adébayo Badirou; Emeka Alfred Clement; Fresnel Lutèce Ontsi Obame; Laté Dzidoula Lawson; Romeo Bujiriri Murhega; Arsène Daniel Nyalundja; Nukunté David Lionel Togbenon; Thierry Alihonou; Yao Christian Hugues Dokponou (Egyptian Journal of Neurosurgery, 2023)
Abstract Background Epidural hematoma constitutes a common condition in neuro-traumatology. If its acute form is well known, the chronic one remains less described. Objective This study aimed to evaluate the epidemiology, clinical presentations, management, and outcomes of chronic epidural hematoma. Methodology Systematic searches of PubMed, Google Scholar, and ScienceDirect were performed from a database searching for all studies reporting chronic epidural hematoma. Pooled statistics were calculated using measures of central tendency and spread. The rank correlation test and the regression test, using the standard error of the observed outcomes as predictor, are used to check for funnel plot asymmetry. Results A total of 3009 studies were identified, of which 95 were included with 359 patients. Chronic epidural hematoma (CEDH) was more common at the intracranial level than spinal level (91.9% vs 8.1%). The average age of onset was 37.2 ± 4.83 years. The common cause found was trauma (n = 279; 77.72%) with 271 (97.1%) cases for the head and 8 (2.9%) cases for the spine. The mean delay between the trauma and the first symptoms was 13.32 ± 1.73 days in intracranial level and 16.38 ± 2.49 days in spinal level. CT scan constituted the main diagnosis tool. The lesion was predominantly located in the temporal region at the intracranial level and lumbar region at the spinal level. Craniotomy and laminectomy constituted the most reported treatment option, respectively, at the intracranial and spinal level. The outcome was commonly uneventful. Correlation and regression tests for publication bias assessment show no significant funnel plot asymmetry with high p value (p = 0.8458 and p = 0.9596, respectively). Conclusion CEDH was commonly related to trauma. Its treatment was mostly surgical at both sites.